3-Piperazinyl propenylidene indolone merocyanines: consecutive three-component synthesis and electronic properties of solid-state luminophores with AIE properties12. (21st June 2017) - Denißen, Melanie; Nirmalananthan, Nithiya; Behnke, Thomas; Hoffmann, Katrin; Resch-Genger, Ute; Müller, Thomas J. J.
Abstract : One-pot insertion-coupling-addition synthesis gives piperazinyl indolones showing aggregation induced emission and crystallization-induced emission enhancement. Abstract : A series of twelve 3-piperazinyl propenylidene indolone merocyanines was synthesized in a one-pot fashion using a consecutive three-component insertion-coupling-Michael addition sequence. Physical-organic treatment of the absorption data of a consanguineous series of this library allows semiquantitative Linear Free Energy Relationships (LFERs) to be established and confirmation of the positive absorption solvatochromicity. All Boc-substituted piperazinyl merocyanines display aggregation induced emission (AIE), which was corroborated for two solvent systems. In particular, crystallization-induced emission enhancement (CIEE) induced by ultrasonication could be shown for a model chromophore by confocal laser scanning microscopy (CLSM).